2014
DOI: 10.2134/jeq2014.01.0017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Selected Bioretention Blends for Nutrient Retention Using Mesocosm Experiments

Abstract: This study compares the performance of three bioretention media blends for N and P removal from simulated urban runoff in experimental mesocosms. TerraSolve, Biofilter, and "VT Mix" (Virginia Tech) were compared with and without vegetation at varying hydraulic residence times (HRTs). Adsorption isotherm experiments were also conducted. TerraSolve and VT Mix included water treatment residuals (WTRs), Biofilter and VT Mix included yard-waste compost (YWC), and TerraSolve included a mix of coir and peat. TerraSol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…Regarding all the pollutants, an average range of removal efficiency can be observed, varying from 20% to almost 50%. This range is low when compared to other studies which also evaluated the laboratory performance and obtained removal rates in the order of 90% (RYCEWICZ-BORECKI; MCLEAN; DUPONT, 2017;CHAHAL;SHI;FLURY, 2016;WANG et al, 2015WANG et al, , 2016LIU et al, 2014;BRATIERES et al, 2008). Finally, an export of pollutants was found for NO 3 , Fe, and Cd.…”
Section: Laboratory Scalementioning
confidence: 62%
See 1 more Smart Citation
“…Regarding all the pollutants, an average range of removal efficiency can be observed, varying from 20% to almost 50%. This range is low when compared to other studies which also evaluated the laboratory performance and obtained removal rates in the order of 90% (RYCEWICZ-BORECKI; MCLEAN; DUPONT, 2017;CHAHAL;SHI;FLURY, 2016;WANG et al, 2015WANG et al, , 2016LIU et al, 2014;BRATIERES et al, 2008). Finally, an export of pollutants was found for NO 3 , Fe, and Cd.…”
Section: Laboratory Scalementioning
confidence: 62%
“…Nevertheless, studies conducted in the laboratory are not limited to metals. Chahal, Shi and Flury (2016), Liu et al (2014) and Bratieres et al (2008) evaluated the nutrient removal in a bioretention system and reported removal efficiency ranging from 80 to 99%.…”
Section: Introductionmentioning
confidence: 99%
“…Embora não constituam propriamente os teores totais, pois o método extrai as quantidades de nutrientes no solo ambientalmente disponíveis, estes valores podem ser considerados como representativos da quase totalidade destes elementos no solo. O uso de extrator fitodisponível ou extrator das quantidaes disponíveis, como EDTA ou HCl, 1,0 M, apenas identificam o potencial disponível para as plantas e não indicam o potencial disponível em termos ambientais (LIU et al, 2014).…”
Section: Resultsunclassified
“…Soils can be a source or sink for nitrogen [7,13]. High levels of organic matter can be mineralized, resulting in higher levels of nitrate.…”
Section: Introductionmentioning
confidence: 99%